Menghadapi Tantangan Bisnis: Optimalisasi Analisis Beban Kerja dan Perencanaan Kebutuhan Tenaga Kerja - Julia Puspita; Arfah; Setya Prihatiningtyas (Business Administration Dept. - Faculty of Social and Political Sciences, Hang Tuah University, 2023)
To overcome fierce competition in the industrial and service sectors, companies strive to maintain their existence and maximize their business activities. However, no matter how perfect the technical and economic aspects are, a company without a qualified workforce will not be able to achieve its set goals. One of the efforts to create human resources that can generate optimal performance is by managing human resources professionally. Workload analysis becomes one of the efforts that companies must undertake to balance workforce needs with company demands and opportunities. It is important to conduct workload analysis and plan workforce needs to maintain workforce performance within the company. This research adopts a qualitative approach that applies an interactive approach, focusing on the interaction between researchers and informants. The focus of this research is to analyze workloads and plan workforce needs. The research subjects consist of three individuals working in the finance field and an HSE Coordinator. Based on the findings and analysis conducted, it can be concluded that there is a workload exceeding the normal limits imposed on the workforce in the finance department. Additional workloads, working hours, and achievement targets beyond responsibilities that are not balanced with compensation and additional workforce will hurt workforce performance in the company.